PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 65 PEKANBARU - Tya Rizki Ardy; Jesi Alexander Alim; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRAKThe mathematics result of fourth grade students of SD Negeri 65 Pekanbaru was too low because students were subjects who geint knowledge so that they were pasive in learning process. The purpose of this study is to Improve Students Mathematics Learning Outcomes throught implementation of direct Learning Model. The research problem is whether the implementation of direct learning model can improve mathematics out comes of fourth grade students of SD Negeri 65 Pekanbaru? Based on the research the results of the study indicated that teacher is activities increased about 84% in the first cycle with a good category to 93.7% in the second cycle with a very good category. Students activites also increased about 56.2% in the first cycle to 93.7% in the second cycle with a very good category. Learning outcomes of students increased 26.31 in UH I of first cycle and increased 88.35 at UH II of second cycle. Based on this research it can be concluded that the implementation of Direct Learning Model can improve mathematics learning outcomes of fourth grade students of SD Negeri 65 Pekanbaru.Keywords : Model , Direct Learning , Math Learning Outcomes